Septic pulmonary artery thrombosis in a child with community acquired pneumonia: A case report - Anil Sachdev; Amrit Ghimire; Neeraj Agarwal; Neeraj Gupta (Wolters Kluwer Medknow Publications, 2019)
Septic pulmonary embolism is a diagnosis seldom considered in children. We present the clinical course of a 6 year-old child with septic pulmonary embolism secondary to community acquired Pseudomonas pneumonia. Chest radiograph revealed bilateral pneumonia and pleural effusion. CT pulmonary angiogram showed hypodense filling defects in pulmonary artery branches along with consolidations. Pseudomonas aeruginosa was isolated in bronchoalveolar lavage culture. Child was treated with IV antibiotics and low molecular weight heparin. Follow up clinical and investigations revealed remarkable improvement.